Mathematics and metacognition in adolescents and adults with learning disabilities - Annemie Desoete (International Electronic Journal of Elementary Education, 2009)
A majority of studies on learning disabilities have focused on elementary grades. Although problems with learning disabilities are life-affecting only a few studies focus on deficits in adults. In this study adults with isolated mathematical disabilities (n=101) and adults with combined mathematical and reading disabilities (n=130) solved tests on procedural calculation and number knowledge, numerical facility and visuospatial skills. Metacognitive skilfulness was assessed through calibration measures, a questionnaire, stimulated recall, and thematic analyses after a qualitative interactive interview with a flexible agenda to discover the interviewee’s own framework of meanings and to avoid imposing the researcher’s structures and assumptions. In our dataset the isolated group (MD) did worse than the comorbid group (M+RD) on mental representation, dealing with contextual information and number knowledge. However the comorbid group did worse on the number sense tasks. No significant differences were found between the MD and M+RD adults for fact retrieval, procedural calculation and visuo spatial tasks. In addition adults with MD overestimated their mathematics results, whereas individuals with M+RD underestimated their results in the calibration task. Moreover, adults with M+RD thought that they were worse on the evaluation of the own results, the evaluation of the own capacities and on monitoring when things went wrong compared with adults in the M+RD group. Thematic analyses revealed that many adults had problems with planning and keeping track of steps and that supporting surroundings were important protective factors towards the chances of success. Consequences for the assessment of metacognition in adults and for the support of adults with mathematical disabilities are discussed.